Phenotypic and biochemical analysis of an international cohort of individuals with variants in NAA10 and NAA15. (1st May 2019) - Cheng, Hanyin; Gottlieb, Leah; Marchi, Elaine; Kleyner, Robert; Bhardwaj, Puja; Rope, Alan F; Rosenheck, Sarah; Moutton, Sébastien; Philippe, Christophe; Eyaid, Wafaa; Alkuraya, Fowzan S; Toribio, Janet; et al.
Abstract: N-alpha-acetylation is one of the most common co-translational protein modifications in humans and is essential for normal cell function. NAA10 encodes for the enzyme NAA10, which is the catalytic subunit in the N-terminal acetyltransferase A (NatA) complex. The auxiliary and regulatory subunits of the NatA complex are NAA15 and Huntington-interacting protein (HYPK), respectively. Through a genotype-first approach with exome sequencing, we identified and phenotypically characterized 30 individuals from 30 unrelated families with 17 different de novo or inherited, dominantly acting missense variants in NAA10 or NAA15 . Clinical features of affected individuals include variable levels of intellectual disability, delayed speech and motor milestones and autism spectrum disorder. Additionally, some subjects present with mild craniofacial dysmorphology, congenital cardiac anomalies and seizures. One of the individuals is an 11-year-old boy with a frameshift variant in exon 7 of NAA10, who presents most notably with microphthalmia, which confirms a prior finding with a single family with Lenz microphthalmia syndrome. Biochemical analyses of variants as part of the human NatA complex, as well as enzymatic analyses with and without the HYPK regulatory subunit, help to explain some of the phenotypic differences seen among the different variants.